Crustal structure beneath western and eastern Iceland from surface waves and receiver functions. - Du, Z.; Foulger, G.R.; Julian, B.R.; Allen, R.M.; Nolet, G.; Morgan, W.J.; Bergsson, B.; Erlendsson, P.; Jakobsdottir, S.; Ragnarsson, S.; Stefansson, R.; Vogfjord, K. (Geophysical Journal International, 2002)
We determine the crustal structures beneath 14 broad-band seismic stations, deployed in western, eastern, central and southern Iceland, using surface wave dispersion curves and receiver functions. We implement a method to invert receiver functions using constraints obtained from genetic algorithm inversion of surface waves. Our final models satisfy both data sets. The thickness of the upper crust, as defined by the velocity horizon Vs= 3.7 km s−1, is fairly uniform at ∼6.5–9 km beneath the Tertiary intraplate areas of western and eastern Iceland, and unusually thick at 11 km beneath station HOT22 in the far south of Iceland. The depth to the base of the lower crust, as defined by the velocity horizon Vs= 4.1 km s−1 is ∼20–26 km in western Iceland and ∼27–33 km in eastern Iceland. These results agree with those of explosion profiles that detect a thinner crust beneath western Iceland than beneath eastern Iceland. An earlier report of a substantial low-velocity zone beneath the Middle Volcanic Zone in the lower crust is confirmed by a similar observation beneath an additional station there. As was found in previous receiver function studies, the most reliable feature of the results is the clear division into an upper sequence that is a few kilometres thick where velocity gradients are high, and a lower, thicker sequence where velocity gradients are low. The transition to typical mantle velocities is variable, and may range from being very gradational to being relatively sharp and clear. A clear Moho, by any definition, is rarely seen, and there is thus uncertainty in estimates of the thickness of the crust in many areas. Although a great deal of seismic data are now available constraining the structures of the crust and upper mantle beneath Iceland, their geological nature is not well understood.